RISK FACTORS FOR SEVERE PRE-ECLAMPSIA IN PREGNANT WOMEN IN RIAU ISLANDS 2019 - Asmarita Jasda; Romalina, Romalina; Elsa Gusrianti (International Journal of Social Science, 2021)
Pre-eclampsia is a specific disorder in pregnancies older than 20 weeks characterized by an increase in blood pressure (hypertension) and the presence of protein in the urine (proteinuria). The incidence of pre-eclampsia/ eclampsia is associated with a low level of maternal education, and others. Tanjungpinang City Hospital, which is the main referral hospital in Tanjungpinang City, noted that pre-eclampsia/eclampsia complications have increased. The purpose of this study is to determine the risk factors for PEB in pregnant women in the Riau Islands region in 2019. This type of research uses descriptive research methods with an approach that includes nursing assessment, diagnosis, intervention, implementation and evaluation of nursing. This research was carried out in the Riau Islands area. The subjects of the study were 30 pregnant women who lived in Berakit village and Pengudang village. From the results of the study, it was found that there was a relationship between age (p-value = 0.01), last education (p-value = 0.01), and a history of hypertension (p-value 0.000) with the incidence of preeclampsia. Meanwhile, in the factors of employment status (p-value = 0.361), parity (p-value = 0.414) and gestational age (p-value = 0.381) there was no significant relationship with the incidence of preeclampsia